Doktrin Predestinasi dan Determinisme: Antara Muktazilah dan Asy’ariyah - Manshur, Fadlil Munawwar; Herlina, N. Hani; Atoillah, Ahmad Nabil (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
In classical Islamic thought, ‘divine predestination’ (qada’ wa’l-qadar) versus ‘human free will’ (ikhtiyar) is one of the most hotly contested topics. This article critically analyses the contribution made to this discourse by the two prominent schools of Islamic theology, the Asharites and the Mu’tazilites, by focusing on a topic that is crucial to the philosophy and theology of theology. This article seeks to properly understand Islamic intellectual history and culture by arguing that the treatment of the two schools of Islamic theology on the issue of qada’ wa’l-qadar and ikhtiyar is innovative, influential, and fundamentally more complex than previously acknowledged. On the subject of free will versus fate, the study’s findings indicate that the Mu’tazilah and Ash’ariyah have made compromises between philosophical, theological (kalam), and esoteric (sûfi) perspectives. Given that the subject matter and methodology of kalam, falsafah, and tasawwûf are frequently considered to be very different or even contradictory, this attitude of accommodation is plainly exceptional.